MENGEMBANGKAN ASSESSMENT DALAM MATEMATIKA MENJADI SUATU INSTRUKSI YANG JELAS BAGI PESERTA DIDIK - Made Adi Nugraha Tristaningrat; Komang Trisna Mahartini (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2022)
This study aims to analyze through the literature related to developing assessment into the form of instruction. there are 4 specific objectives this is done, among others: 1) monitor student progress; 2) make instructional decisions; 3) evaluate student achievement; 4) evaluate the program. Instruction-based assessment can measure not only student learning outcomes, but must be able to measure how well students understand mathematical concepts so that they can be used in everyday life. This study uses literature analysis and produces several instruments that can be used as a reference by educators in teaching mathematics to students. In general, the implementation of the assessment is important in the learning process. A good assessment is an assessment that not only measures learning outcomes, but also requires revision of the teaching design itself. Classification or classification of assessments in the field of education is very diverse. This very diversity is due to the different points of view in doing these classifications. In this case, the classification of the assessment in question is formative and summative assessment. Specifically in the field of mathematics, there is an Assessment Standard by the NCTM (National Council of Teachers of Mathematics) which states that assessment is the process of gathering evidence about students' knowledge, ability to use, and disposition towards mathematics and drawing conclusions from that evidence for various purposes.Keywords: Assessment, Mathematics, and NCTM